2009
DOI: 10.1021/ac900561r
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Detection of DNA Sequences Using the Volume-Amplified Magnetic Nanobead Detection Assay

Abstract: The possibility for conducting multiplex detection of DNA-sequences using the volume-amplified magnetic nanobead detection assay [Stromberg, M.; Goransson, J.; Gunnarsson, K.; Nilsson, M.; Svedlindh, P. and Strømme, M. Nano Lett. 2008 , 8, 816-821] was investigated. In this methodology, a batch consisting of a mixture of several sizes of probe-tagged magnetic beads was used for detection of several types of targets in the same compartment. Furthermore, a nonlinear least-squares deconvolution procedure of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 28 publications
1
56
1
Order By: Relevance
“…A widely used detection scheme is based on Brownian relaxation. 82,83 Each MNP in suspension undergoes thermal rotation with a timescale ( τ B ) proportional to the particle’s hydrodynamic volume. Such thermal rotation affects the frequency-dependent magnetic susceptibility ( χ ) of the MNPs; the quadrant component of χ has its peak at the excitation frequency of 1/ τ B .…”
Section: Magnetometers For Signal Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A widely used detection scheme is based on Brownian relaxation. 82,83 Each MNP in suspension undergoes thermal rotation with a timescale ( τ B ) proportional to the particle’s hydrodynamic volume. Such thermal rotation affects the frequency-dependent magnetic susceptibility ( χ ) of the MNPs; the quadrant component of χ has its peak at the excitation frequency of 1/ τ B .…”
Section: Magnetometers For Signal Detectionmentioning
confidence: 99%
“…Binding of target molecules to MNPs changes the hydrodynamic diameter (and hence τ B ), and induces a shift in the peak position. Magnetic susceptometry has been used to detect soluble proteins, 84 DNA, 82 and bacteria, 85 with signals measured via induction coils or SQUID. Recently, Park et al demonstrated a compact susceptometer for Brownian relaxation measurement (Fig.…”
Section: Magnetometers For Signal Detectionmentioning
confidence: 99%
“…[15] More specific challenges include: making biosensors compatible with biological matrices, so that they can be used in complex biological samples or even in vivo; [16,17] fabrication of viable biosensors that can operate within confined environments such as inside cells; [17] and multiplexing biosensors so multiple analytes can be detected on one device. [18][19][20] Various kinds of zero-, one-, two-, and threedimensional nanomaterials are helping to meet these challenges. Examples of such materials include semiconductor quantum dots, [21] metallic nanoparticles, [22] metallic or semiconductor nanowires, [14,23] CNTs, [24,25] nanostructured conductive polymers or nanocomposites thereof, [26] mesoporous materials, [27] and various other nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we focus on a sophisticated and sensitive method that exploits the change of the Brownian rotation dynamics of magnetic nanobeads (MNBs) when these attach to DNA coils (Strömberg et al, 2009;Strömberg et al, 2008aStrömberg et al, , 2008b. Using measurements of the magnetic susceptibility of a suspension of MNBs mixed with the sample containing DNA coils, sensitivities in the pM range have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%